Padrões de distribuição dos braconidae (hymenoptera, ichneumonoidea) em áreas de cerrado no Brasil e de savana em Angola - Timóteo, Ferreira Manuel (Universidade Federal de São Carlos, 2020)
The present work had as main objective to study the distribution of Braconids (Hymenoptera) in general the Parasitoids in two different continents: American (Brazil) and African (Angola), through sampling collected with malaise traps in the southeastern savannah area do Brasil (Estação Ecológica de Jataí, Luiz Antônio), SP, in 2013 and 2014 and in the savannah area in Angola (Quiçama National Park, Luanda, with an area of 996,000 hectares, in 2019). At the Ecological Station of Jataí (EEJ), 923 specimens of Braconidae were collected, created in 23 subfamilies; in the Quiçama National Park (PNQ), 1537 examples of Braconids created in 17 subfamilies were collected. In view of the sessions carried out, in the PNQ there was a greater increase in the level of subfamilies in the PNQ Cardiochilina, Agathidinae, Microgastrinae, and Rogadinae, in the EEJ, for example, in the 1975 Palma average classification. (Males and children were used collectively, without predominance of the same). No PNQ with higher gender values were found among Cardioquilos (202) and Disophrys (233); in EEJ the most abundant were the Glyptapanteles (95) and Aleiodes (70), mainly in the rainy season. In the EEJ, he found a total of 33 genera classified as intermediate and 44 as rare, no PNQ was classified as 12 as intermediate and 39 as rare. The highest rates of Diversity and Equity were found in the EEJ. In both locations, there was no saturation on the collector curve. No new material from the PNQ was found, a new species of Adelius Haliday (Cheloninae) that was captured and sent for publication. In particular for the Afrotropical fauna of Braconidae, this work represents a contribution and a starting point for further studies in the region of Angola.
Distribution patterns of braconidae (hymenoptera, ichneumonoidea) in cerrado areas in Brazil and savana in Angola
Keywords: Diversidade; Savana; Cerrado; Braconidae; Afrotropical; Neotropical; CIENCIAS BIOLOGICAS::ZOOLOGIA::TAXONOMIA DOS GRUPOS RECENTES